Subgroup analysis of accreta, increta and percreta cases using acoustic radiation force impulse elastography. Issue 5 (9th March 2020) - Bayramoğlu Tepe, Neslihan; Gelebek Yilmaz, Feyza; Bozdag, Zehra; Uğur, Mete Gürol
Abstract: Objective: To compare acoustic radiation force impulse (ARFI) elastography values and histopathological diagnoses (accreta, increta, percreta) in patients suspected of having abnormal placental invasion (API). Materials and methods: This prospective study included 54 patients in the third trimester with a history of caesarian section (CS) and API based on gray scale and Doppler ultrasonography (USG) and 35 healthy controls. Patients underwent ARFI elastography preoperatively. Elastography measurements of the fetal and maternal sides of the placenta were compared to histopathology. Results: Patients had higher maternal‐side, fetal‐side and average elastography values ( P = 0.001). Intraoperatively, eight patients (14.8%) showed abnormal cervical canal invasion and 46 (85.2%) bladder and/or parametrial invasion. Eight patients underwent CS + placental‐bed suture, 11 CS + excision of the lower segment, and 35 caesarean‐hysterectomy. Histopathology of lower segment excision/caesarian‐hysterectomy patients determined 10 (21.7%) accreta, 10 (21.7%) increta and 26 (56.6%) percreta cases. ARFI values were highest in the percreta subgroup. The increta subgroup showed higher ARFI values than the accreta subgroup but maternal‐side, fetal‐side and average ARFI values were not significantly different across the subgroups ( P  > 0.05). The cut‐off values for average, peripheral and central elastography were determined as >0.90, >0.76, >0.98 (m/s) with sensitivities of 98, 64, 98% and specificities of 85, 80, 91%, respectively. Conclusion: ARFI elastography can detect API. However, it cannot determine invasion depth reliably. More studies with subgroup analyses are warranted to reveal its usefulness for invasion depth.